(untitled) (Islas, 2024)
Introduction: Is invited to think of literary criticism as an indispensable element for the mobility and development of literature. Opinions are expressed about the critical exercise required by monumental and territorialized works such as Neruda’s Canto general. Methods: The proposal has an interdisciplinary approach where Philosophy, Literature, Theory of literary criticism and cultural studies converge and it’s based on the categories proposed by Deleuze and Guattari’s in A Thousand Plateaus Capitalism and Schizophrenia (2002). Results: The article proposes that the critical exercise around Neruda must assume the nomadic, to notice the fertility of certain territories that move away from the molar postures that have characterized Nerudian criticism. The results are evidenced from the analysis of the critical attitude that the researcher and professor Mario Rodriguez Fernandez has developed around the Chilean poet. Conclusions: Assuming the nomadic in the critical exercise that implies appropriating the relations between literature and philosophy, anthropology and cultural studies. the incorporation of several disciplines offers theoretical and methodological tools that favor the critical exercise.